Chinese Migrants as a Social Group in Socio-Humanitarian Knowledge: Theory and Practice - Irina A. Shchetkina; Jiang Dan; Dina B. Sundueva (Гуманитарный вектор)
The modern world is characterized by dynamism, changing social, economic, and political realities. Migration is becoming one of the phenomena developing rapidly due to new forms of communication, digital ways of transmitting information and interaction. The result of migration processes is the creation of social groups of migrants in the host country, which perform the functions of ensuring the adaptation of their members in a new social space for them. In this regard, the theoretical study of migrants as a social group, the description of the functional characteristics of Chinese migrants as a social group is relevant. The purpose of the article is to identify in scientific concepts and social reality the main characteristics and functions of migrants as a social group, to highlight the system-forming features of the social group of Chinese migrants. In the article, social groups are considered as associations of people interacting with each other in the course of their life on the basis of traditional and innovative values, norms and rules of behavior, associations of people performing certain functions in society. As a result of the conducted research, the system-forming features of the social group of Chinese migrants are identified, including interaction, consideration of oneself as a member of this social group, development of norms and rules of behavior, common goals and objectives of activity, etc. The study showed that the social groups of Chinese migrants mean diasporas, social communities, enclaves. The theoretical analysis of the social group allows us to conclude that there is no unified understanding of the concept of “social group” in the scientific literature. This is determined by the dynamism of the social reality itself, which makes certain adjustments to the research of the social group, as well as by the constant change in the role of social groups in the space of their life activity.